The effect of individual elements of alkali aluminosilicate glass on scratch characteristics: A molecular dynamics study - Ahn, Yong Nam; Harris, Jason T (Journal of non-crystalline solids, 2020)
•Deformation of alkali aluminosilicate glass during scratch process is investigated.•Friction coefficient reduces with increasing the elasticity of glass substrates.•Role of each element in response to applied stress during scratching is identified.•Response of alkali elements to applied stress changes dramatically by ion exchange. Flaws on glass surfaces significantly reduce mechanical strength by concentrating applied stresses on their tips. Since these surface defects are formed by surface contact loading, such as scratching, it is crucial to enhance scratch resistance for high mechanical strength. In this regard, we investigate contributions of individual elements of alkali aluminosilicate glass (15Na2O∙5MgO∙11Al2O3∙69SiO2) to surface deformations during scratching by utilizing molecular dynamics simulations. It is found that the friction coefficient is inversely proportional to the amount of elastic deformation. Analyses of local atomic structure demonstrate that Mg and Al mainly contribute to the elastic response, whereas Na tends to heavily participate in plastic deformation. Chemical strengthening of glass further enhances the elastic behavior of Mg and Al and alters the characteristic of alkali elements from plastic to elastic participation. Atomic-level understanding of individual roles of glass elements is expected to contribute to developing advanced glasses with high surface damage resistance.